2008
DOI: 10.1097/mpa.0b013e31815d9bad
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the TNF, CD14, and HSPA1B Genes in Patients With Acute Alcohol-Induced Pancreatitis

Abstract: The TNF, CD14, and HSPA1B polymorphisms studied seem not to play a role in determining the severity of AP or the risk of alcohol-induced AP and thus do not serve as a tool for predicting disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
0
8
1
4
Order By: Relevance
“…1) (Balog et al, 2005;Bendicho et al, 2005;Beranek et al, 2003;de-Madaria et al, 2008;Farkas et al, 2007;Howell et al, 2005;Ozhan et al, 2010;Powell et al, 2001;Schneider et al, 2003Schneider et al, , 2004Talar-Wojnarowska et al, 2009;Tukiainen et al, 2008;Zhang et al, 2003). There were 12 case-control studies with 1569 cases and 1330 controls concerning TNF-α −308G>A polymorphism and susceptibility to pancreatitis (Balog et al, 2005;Bendicho et al, 2005;Beranek et al, 2003;Farkas et al, 2007;Howell et al, 2005;Ozhan et al, 2010;Powell et al, 2001;Schneider et al, 2003Schneider et al, , 2004Talar-Wojnarowska et al, 2009;Tukiainen et al, 2008;Zhang et al, 2003), 4 studies with 480 cases and 302 controls concerning TNF-α −238G>A polymorphism and susceptibility to pancreatitis (Beranek et al, 2003;Ozhan et al, 2010;Schneider et al, 2003Schneider et al, , 2004, and 5 studies with 555 cases of mild AP and 400 cases of severe AP concerning TNF-α −308G>A polymorphism and severity of AP (Balog et al, 2005;de-Madaria et al, 2008;Powell et al, 2001;Tukiainen et al, 2008;Zhang et al, 2003). Schneider et al (2003Schneider et al ( , 2004 used the duplicate control group versus different case groups in two publications from their institute.…”
Section: Resultsmentioning
confidence: 99%
“…1) (Balog et al, 2005;Bendicho et al, 2005;Beranek et al, 2003;de-Madaria et al, 2008;Farkas et al, 2007;Howell et al, 2005;Ozhan et al, 2010;Powell et al, 2001;Schneider et al, 2003Schneider et al, , 2004Talar-Wojnarowska et al, 2009;Tukiainen et al, 2008;Zhang et al, 2003). There were 12 case-control studies with 1569 cases and 1330 controls concerning TNF-α −308G>A polymorphism and susceptibility to pancreatitis (Balog et al, 2005;Bendicho et al, 2005;Beranek et al, 2003;Farkas et al, 2007;Howell et al, 2005;Ozhan et al, 2010;Powell et al, 2001;Schneider et al, 2003Schneider et al, , 2004Talar-Wojnarowska et al, 2009;Tukiainen et al, 2008;Zhang et al, 2003), 4 studies with 480 cases and 302 controls concerning TNF-α −238G>A polymorphism and susceptibility to pancreatitis (Beranek et al, 2003;Ozhan et al, 2010;Schneider et al, 2003Schneider et al, , 2004, and 5 studies with 555 cases of mild AP and 400 cases of severe AP concerning TNF-α −308G>A polymorphism and severity of AP (Balog et al, 2005;de-Madaria et al, 2008;Powell et al, 2001;Tukiainen et al, 2008;Zhang et al, 2003). Schneider et al (2003Schneider et al ( , 2004 used the duplicate control group versus different case groups in two publications from their institute.…”
Section: Resultsmentioning
confidence: 99%
“…Rahman et al [34] reported that the -260 genotype was not associated with development of AP, the severity index, peak CRP, monocytic CD14 density, or sCD14 concentration in White Caucasians. Tukiainen et al [35] reported from Finland that the allele frequency did not differ between AP patients with organ failure and those with mild disease, patients with alcoholic AP, or those with biliary AP. Thus, it has been increasingly recognized that the -260C/T polymorphism is not associated with AP, and our results further support the notion.…”
Section: Discussionmentioning
confidence: 97%
“…There are several studies examining the association of AP with the -260C/T polymorphism in various populations [32][33][34][35]. Chao et al [32] reported from Taiwan that patients with alcoholic AP had more -260C alleles than controls and than non-alcoholic AP.…”
Section: Discussionmentioning
confidence: 99%
“…Ген који га кодира полиморфан је, а највише испити-ване варијације су на нивоу промотора, и то -308G>A и -238A>G 9 . Иако има и супротних закључака 17,18 , многа досадашња истраживања указала су на повезаност поменутих поли-морфизама са тежином клиничке слике пан-креатитиса 3,5,9,15 . Наиме, значајна разлика у дистрибуцији полиморфизма -308G>A код пацијената са тешком клиничком сликом акутног панкреатитиса и септичним шоком у поређењу са лакшим пацијентима указује на повезаност ове варијације са тежином обо-љења 8 .…”
Section: генетски полиморфизAm медијатора запаљењаunclassified